Managing Risk to Increase Efficiency and Reduce Poverty - Alderman, Harold (Washington, DC: World Bank, 2012)
Uninsured risks remain extensive in agriculture and rural life--and unabated, they have substantial efficiency and welfare costs. They perpetuate rural poverty and are a continuing source of new poor. Indeed, they remain a major cause of under-investment and mis-investment in agriculture. While there is a wide range of highly innovative new approaches, these are largely untested. More experimentation and systematic evaluation of innovations such as risk-reducing technology, privately-provided market insurance and safety net programs remain a priority in using agriculture for development.